Fundamentalismo religioso e educação em um contexto de ajuste fiscal e de avanço da extrema direita - Martins, Ivan Carlos Costa (2024)
The present Thesis analyzes to what extent the educational proposals of religious fundamentalists, socially related to the far right and neoliberalism, exclude the perspective of a critical and emancipatory formation and strengthen the interests of an education for the formation of the religious human being, the alienated individual, and the subject available to work under capitalist forms. The attempt by the capitalist system to train the human being, especially trying to manipulate their subjectivity and orient it in favor of the social development of capital, explains why the far right and religious fundamentalism are advancing and why attacks on education are deepening. The present research has as its general theme the social relationship between religion and education, precisely the Brazilian evangelical religious fundamentalism and educational policy, and therefore critically considers possible fundamentalist projects for education, articulated with fiscal adjustment and the far right. The general objective of the research is to analyze the ideology of religious fundamentalists expressed in educational projects, in the light of historical-dialectical materialism. To this end, it presents the main aspects of the formation and cultural, economic, educational, religious, and social development of Brazilian society; examines the constituent elements of the neoliberal model in a context of crisis of capital and its relations with education and religion; understands Bolsonarism as a sociopolitical movement formed by a power consortium in an international and national context of the advancement of the far right and religious fundamentalism; describes the genesis, historical development, and social function of religious fundamentalism in society and in class struggles; and analyzes the proposals, plans, and projects that evangelical fundamentalism has for education, using homeschooling and the School Without Party as examples. As theoretical-methodological principles, the work is based on historical dialectical materialism, with emphasis on the categories of dialectic, history, ideology, materialism, and praxis. The research presents, among its results, anti-communism and irrationalism as didactic syntheses of the dialectic of negation of values; and as didactic synthesis of affirmation of values, the concepts of authority, business, fanaticism, war, freedom, fear, rationality, sacrifice, and truth.